Formation of student character in preparation for the Branch Jamboree Event - Arya Farhan Azhari; Aulia Nurannisa; Aulia Shabrina Fitri; Nur Fitria Ramadhani (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
Community Service or Kuliah Kerja Nyata (KKN) is a student learning process that is carried out directly in a community group. One of them is by directly participating in the field of education related to the formation of student character through the scout training program. The formation of student character aims to enable students to utilize the knowledge and skills they have wisely. This service is carried out with the direct involvement of KKN participants in the preparation for the jamboree. The implementation activities are carried out every day within 2 weeks. The types of activities provided include semaphore training, cheer creativity, and making emergency stretchers, tents, and gates. The form of learning carried out is dominated by practical activities in the field rather than providing theory. In its implementation, UPI KKN students divided themselves into 4 small groups according to their fields to maximize the teaching process. The results achieved from this KKN program include the emergence of leadership values, togetherness, independence, and discipline in students at SDN Sukadami. SDN Sukadami students contributed to the Wanayasa District Branch Jamboree event.   Abstrak Kuliah Kerja Nyata (KKN) adalah proses pembelajaran mahasiswa yang dilakukan secara langsung di suatu kelompok masyarakat. Salah satunya adalah dengan terjun langsung di bidang pendidikan terkait pembentukan karakter peserta didik melalui program pelatihan Pramuka. Pembentukan karakter peserta didik ini bertujuan agar peserta didik mampu memanfaatkan pengetahuan dan keterampilan yang mereka miliki dengan bijak. Pengabdian ini dilakukan dengan keterlibatan langsung peserta KKN ke dalam persiapan untuk jambore. Kegiatan pelaksanaan dilakukan setiap hari dalam rentan waktu 2 minggu. Adapun jenis kegiatan yang diberikan seperti pelatihan semaphore, kreativitas yel-yel, pembuatan tandu darurat, tenda, dan gapura. Bentuk pembelajaran yang dilakukan didominasi oleh kegiatan praktik di lapangan ketimbang pemberian teori. Pada pelaksanaannya mahasiswa KKN UPI membagi diri menjadi 4 kelompok kecil sesuai dengan bidangnya untuk memaksimalkan proses pengajaran. Hasil yang dicapai dari program KKN ini seperti timbulnya nilai-nilai kepemimpinan, kebersamaan, kemandirian hingga kedisiplinan pada diri peserta didik di SDN Sukadami. Peserta didik SDN Sukadami berkontribusi dalam acara Jambore Ranting Kecamatan Wanayasa. Kata Kunci: jambore; Kuliah Kerja Nyata; pengabdian masyarakat; Pramuka; SDGs